2013
DOI: 10.1080/15287394.2013.848394
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression and Growth as Indicators of Effects of the BPDeepwater HorizonOil Spill on Spotted Seatrout (Cynoscion nebulosus)

Abstract: The BP Deepwater Horizon oil spill has great potential to negatively affect estuarine fish populations. In order to assess possible impacts of this event, a series of sublethal lab experiments were performed, using the economically and ecologically important species spotted seatrout (Cynoscion nebulosus). Larval and juvenile spotted seatrout were exposed to sublethal concentrations of high energy water accommodated fraction (HEWAF), chemically enhanced water accommodated fraction (CEWAF), or dispersant alone i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Recent investigations by Garrido et al (2015) support these findings by reporting that smaller size at hatch resulted in an increased mortality rate later in life. An upregulation of production of cytochrome P-4501A (CYP1A) in teleosts is a reliable bio-indicator of exposure to PAH or crude oil (van der Oost et al 2003;Brewton et al, 2013). Field studies found significant upregulation of cyp1a in the Gulf killifish in oiled areas (Whitehead et al, 2011;Dubansky et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations by Garrido et al (2015) support these findings by reporting that smaller size at hatch resulted in an increased mortality rate later in life. An upregulation of production of cytochrome P-4501A (CYP1A) in teleosts is a reliable bio-indicator of exposure to PAH or crude oil (van der Oost et al 2003;Brewton et al, 2013). Field studies found significant upregulation of cyp1a in the Gulf killifish in oiled areas (Whitehead et al, 2011;Dubansky et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In feral pink salmon, embryonic stage exposure to weathered crude oil resulted in weight reduction following 200-300 days (Heintz et al 2000). Brewton et al (2013) reported growth reduction of spotted sea trout following 2010 BP/ Deep Water Horizon oil spill in northern Gulf of Mexico. It is notable that the growth was affected in juvenile Oreochromis niloticus similar to marine fish responses to prolonged crude oil exposure.…”
Section: Discussionmentioning
confidence: 99%
“…However, the whole crude as a toxicant mixture will depict a more realistic picture. Crude oil effects on teleosts span from cytochromes P450 gene induction (Carls et al 2005;Brewton et al 2013), oxidative stress (Roberts et al 2006) and genotoxicity (Harvey et al 1999;Pietrapiana et al 2002) to growth retardation (Brewton et al 2013), reproduction failure (Brannon et al 2012) and teratogenicity (Heintz et al 1999;Incardona et al 2013). In addition, erythrocyte nuclear abnormalities (ENA) have been reported in finfish exposed to crude oil (Barsiene et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…To date several publications have used the HEWAF preparations to conduct toxicity Brewton et al, 2013;Incardona et al, 2014;Mager et al, 2014). One commonality on all these reports is the use of the commercial blender that allows the preparation of larger volumes of dispersions in a systematic fashion using weathered oils; however, there are also significant differences in the loadings (from not reported to 50 mg/L to 1 g/L), the preparation protocols (30 seconds and 2 minute mixing times) and important differences in the times where samples were taken for analysis with respect to their introduction to the testing containers (from immediately after loading to the separatory funnel to 1 hour after settling).…”
Section: Stability Of Different Oil Loading Preparations With Timementioning
confidence: 99%
“…Recently, new methods for the preparation of high-energy water accommodated fractions (HEWAFs) which consist of the formation of oil containing exposure media in the absence of chemical dispersants for both source and weathered oils have been described (Brette et al, 2014;Brewton et al, 2013;Incardona et al, 2013;Jung et al, 2013;Mager et al, 2014). These methods, invariably involve turbulent mixing of oil in seawater followed by a settling period to remove resurfacing oil droplets from the exposure media.…”
Section: Introductionmentioning
confidence: 99%